How Does Affective Brand Experience Customer Loyalty to A Brand of Menstruation Medicine? - Budiman, Bayu; Kuatiawan, Unggul (Jurnal Ilmiah Wahana Pendidikan, 2024)
In developing countries, women at all levels of society (i.e. upper, middle and lower classes) are not sufficiently aware of menstrual hygiene management. The aim of the research is to determine the factors that can influence attitudinal loyalty and behavioral loyalty by encouraging brand love and brand trust through affective brand experience. The data in this study used a survey method with a questionnaire conducted online, respondents used a purposive sampling method in the Jakarta area, with the sample criteria being women aged 20 to 43 years who were Softex customers. For analysis using factor analysis and structural equation modeling (SEM) with the Lisrel application. The results of this study show that there is a positive relationship between affective brand experience and brand love and brand trust and influences attitudinal loyalty and behavioral loyalty. The managerial implication is that in increasing loyalty, attitudes and behavior, marketers need to pay attention to customer trust in a brand because it has been proven that trust has the most significant influence on the encouragement of customer experience in using Softex brand sanitary napkins.